From Pseudo to Genuine Sustainability Education: Ecopedagogy and Degrowth in Business Studies Courses - Helen Kopnina; Timothy Bedford (Australian Journal of Environmental Education)
This article surveys critical scholarship that links the literature on sustainable business education and education for sustainable development goals (ESDG). It is assumed that ESDG is desirable in the business curriculum. However, it is argued here that ESDG erroneously fosters the illusion of successfully combining economic growth, social justice, and environmental protection, foregrounding “sustained and inclusive economic growth”, which is often dependent on the increased consumption of natural resources. ESDG rarely addresses industrial expansion that jeopardizes the opportunity for the resolution of environmental crises, ignoring the intrinsic value of nonhuman species and ecosystems and masking the root causes of unsustainability. ESDG places heavy emphasis on economic and social aspects of sustainability, at the cost of the environment. By contrast, some earlier forms of environmental education recognize the limits to growth and emphasize environmental integrity as a foundation for both social and economic activity. This article emphasizes the need to re-orientate ESDG towards genuine sustainability of ecopedagogy in the context of business education, emphasizing transformative business models based on degrowth, circular economy, and steady-state economy. It is argued that a more explicit pedagogical re-orientation towards the recognition of planetary boundaries, as well as toward a less anthropocentric focus is needed.